Family environment as means of preservation, strengthenings of health of students and formation of self-preservation behavior - Z. I. Tyumaseva; I. L. Orekhova (Вестник Мининского университета, 2019)
Introduction: in the article the family environment as a basis of physical, moral and intellectual development of the child and also preservation, strengthening of physical and mental health is considered. Results of diagnostic testing regarding the relation of parents of school students to a healthy lifestyle as a factor of wellbeing of the children are presented; influence of family on formation at children of the sensual and esthetic, informative, rational and consumer relations to the nature and a responsible attitude to the health. The article purpose is to prove that the family environment plays a huge role in preservation and promotion of health and formation of a healthy lifestyle of the child.Materials and methods: in the course of research activity the analysis of scientific literature on the problem of family education, the family environment, educational potential of family and socialization of the child is carried out. The diagnostic techniques including testing, questioning, the questionnaire, mutually estimation and also pedagogical observation and use of results of educational potential of family in pedagogical activity are used. The mathematics and statistics analysis allowed to generalize the obtained data of diagnostic work. The research is conducted on the basis of boarding school №8 of the Kopeisk city district of Chelyabinsk region and the Southern Ural state humanitarian and pedagogical University.Results: The study gives evidence that the influence of family on raising the children with sensual and esthetical, informative and rational attitude to the nature is the key to their moral and mental health. Scientific ideas of the family environment are expanded, author's definition of the key concept "family environment" is given and its uniqueness at the initial stage of socialization of future citizen of the country is emphasized. The main components of educational potential of family among which parental installations possess a powerful incentive for promotion of influence of the family environment on preservation and promotion of health of children are characterized. Results of the conducted diagnostic testing are described.Discussion and Conclusions: it is emphasized that the family environment is capable of making the foundation of a responsible attitude to the health of the children and promotes preservation and promotion of health, formation of self-preservation behavior.The conclusion is drawn that cognitive, behavioral, moral, ethical components of the family environment are necessary for forming of the positive relations of parents and their children. The family environment is a basis for socialization of the child and formation of a healthy lifestyle, self-preservation behavior.Highlights:-         the concept "family environment" is defined;-         the main components of educational potential of family are characterized;-         influence of family on formation the children’s sensual and esthetic, informative and rational attitude to the nature as bases of moral and mental health is proved;-         results of diagnostic testing are presented.